2018
DOI: 10.5897/jat2018.0309
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure and corporate financial distress of manufacturing firms in Nigeria

Abstract: This paper investigated the effect of capital structure on corporate financial distress of manufacturing firms in Nigeria by employing panel corrected standard error (PCSE) technique. The variables used in the study are corporate financial distress, capital structure, firm size, assets tangibility, revenue growth, profitability and age of firms. The outcome of the research reveals that capital structure affects corporate financial distress negatively while company age from listing years, profitability and asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 22 publications
7
26
0
3
Order By: Relevance
“…Research findings by Tesfamariam (2014) revealed that there is an existence of a positive link between profitability and financial distress. Similar finding was also found by Ikpesu and Eboiyehi (2018) while studies by Thim et al (2011) revealed that profitability negatively affects financial distress. Research work of Baimwera and Murinki (2014) indicates that profitability negatively affects financial distress.…”
Section: Profitabilitysupporting
confidence: 85%
See 3 more Smart Citations
“…Research findings by Tesfamariam (2014) revealed that there is an existence of a positive link between profitability and financial distress. Similar finding was also found by Ikpesu and Eboiyehi (2018) while studies by Thim et al (2011) revealed that profitability negatively affects financial distress. Research work of Baimwera and Murinki (2014) indicates that profitability negatively affects financial distress.…”
Section: Profitabilitysupporting
confidence: 85%
“…In assessing the specific firm determinants of corporate financial distress, the dependent variable employed in the study is the Altman Z score (AMZ) which is used in measuring financial distress. The Altman Z score is used in measuring a firm financial health by predicting the likelihood that a firm will become distress within a 2 year period (Cheluget, 2014;Kristanti, 2015;Kristanti et al, 2016;Eboiyehi and Ikpesu, 2017;Ikpesu and Eboiyehi, 2018). When the z score is greater than 2.9, the firm is in a safe zone, if the z score is between 1.23 and 2.9, is an indication that the firm is in a grey zone but if the z score is below 1.23, the firm is regarded to be in a distress zone.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The coefficient of the variable x4 is positive and statistically significant (p-value <0.05) indicating that high leveraged firms face financial distress more often than firms with low ratio of total liabilities to total assets. However, Ikpesu and Eboiyehi (2018) argue that the ratio of Long term loans to total assets has negative impact on financial distress. This is because firms that received long term loan are expected to be positively evaluated from their lenders/creditors (institutions or banks).…”
Section: Resultsmentioning
confidence: 99%